PENINGKATAN KETERAMPILAN MENULIS TEKS NARASI MENGGUNAKAN MODEL READ, ANSWER, DISCUSS, EXPLAIN, AND CREATE (RADEC) DI KELAS IV SD NEGERI 20 INDARUNG KOTA PADANG - Natasya Rey Fadila; Adrias; Nur Azmi Alwi; Inggria Kharisma (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to improve narrative text writing skills among fourth-grade students at SD Negeri 20 Indarung, Padang City, through the implementation of the RADEC (Read, Answer, Discuss, Explain, and Create) learning model. The study was motivated by the low writing achievement of students, with only 33.33% reaching the minimum learning completion criteria and a class average of 69.73, caused by unsystematic lesson planning, teacher-centered instruction, and low student motivation in writing. This research employed a Classroom Action Research (CAR) design based on the Kemmis and McTaggart model, implemented in two cycles, each consisting of four stages: planning, acting, observing, and reflecting. The subjects were 30 fourth-grade students. Data were collected through test and non-test techniques and analyzed both qualitatively and quantitatively. The results showed a consistent improvement across cycles. In Cycle I Meeting 1, the average writing score was 75.28 with 53.33% completion, increasing to 80.28 with 70% completion in Meeting 2. In Cycle II, the average score rose significantly to 88.06 with a classical completion rate of 86.67%, surpassing the predetermined success indicator of 80%. These findings indicate that the RADEC learning model is effective in improving fourth-grade students' narrative text writing skills.